POSITIVE THINKING, RELATIONSHIP TO RESPECT TOWARD OTHERS AMONG KOYA UNIVERSITY TEACHERS - Shahen; Paiz Saber (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ)
The aim of this study is to investigate the level of positive thinking and respect for others in general among teachers of Koya University, as well as reveal the level of each of these variables according to demographic variables (gender, faculty, academic degree). It also aims at finding a relationship between positive thinking and respect for others in the study sample. The research population consisted of 383 male and 136 female teachers. The sample was randomly selected from 100 male and female teachers. The study included measures of positive thinking and respect for others used, Statistical software (SPSS) was used to present and analyze the data. the most important statistical techniques used (mean, standard deviation, T test for two independent samples, Anova, Normal, and Pearson correlation) The results showed that Koya University teachers have high positive thinking above the average level, there is no statistically significant difference in their level of positive thinking according to the variables (gender, faculty, academic degree). The level of respect for others among teachers of Koya University is high and there is no statistically difference in the level of respect for others according to the variables (gender, faculty, academic degree). In light of the results, several recommendations were made.